Cryptomenorrhea due to imperforate hymen presenting with urinary retention - Pal, Srabanti; Hafizur Rahman; Paarth Vaish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Cryptomenorrhea is a condition where menstruation occurs but is not visible due to obstruction of the outflow tract. One of the most common causes causing primary amenorrhoea and cryptomenorrhea include imperforate hymen. This condition usually presents in adolescent girls with cyclical abdominal pain and primary amenorrhoea. Though it usually presents as an isolated abnormality it may be associated with genetic conditions such as Mayer-Rokitansky-Kuster-Hauser syndrome. The diagnosis is usually confirmed on the basis of grayscale ultrasound however magnetic resonance imaging may be required to diagnose associated mullerian abnormalities. Once the diagnosis is confirmed the management is usually consist of virginity preserving hymenotomy. We here present case of an adolescent girl who presented with primary amenorrhea, abdominal pain and urinary retention. The clinical examination showed well developed secondary sexual characters (Tanner stage 4), distended abdomen and bulging introitus. Grayscale ultrasound and magnetic resonance imaging showed hematocolpos. Patient was planned for resection of hymen and a cruciate incision was given over the hymen and around 700 ml of collected blood was drained. Eversion and suturing of edges of incision was done to maintain patency of outflow tract. During follow up visit at 3 months patient was symptom free with regular menses.